Maxillary aggressive chondrosarcoma: A rare and challenging case - Fadila Kouhen; Malak Chahid; Reyzane El Mjabber; Othmane Bensalah; Meryem Naciri; Hanae El Gouach; Othmane Kaanouch; Najwa Benslima; Rajaa Karmi; Youssef Mahdi; Basma El Khannoussi; Mohammed Afif (Radiology Case Reports)
Chondrosarcomas represent 20%-30% of primary malignant bone tumors, but only about 1% occur in the head and neck region. Maxillary chondrosarcomas constitute a mere 5.76% of head and neck cases, predominantly affecting adults between the second and sixth decades of life. Symptoms, including facial swelling, pain, and nasal obstruction, often lead to delayed diagnoses and increased tumor aggressiveness. This case report details a 45-year-old Moroccan male with an aggressive maxillary chondrosarcoma presenting as a progressive left cheek swelling accompanied by significant pain and vision impairment. Imaging studies revealed a large, lytic maxillary lesion, and biopsy confirmed a low-grade chondrosarcoma. Given the tumor's unresectability, the patient underwent radiotherapy, receiving a total dose of 70 Gy with modest reduction in tumor size but ultimately developed metastatic pulmonary lesions, leading to palliative chemotherapy. Despite aggressive management, the patient succumbed after the fourth cycle of chemotherapy. This case underscores the importance of timely diagnosis and multidisciplinary collaboration in managing maxillary chondrosarcomas, highlighting the challenges posed by their aggressive nature and the need for long-term surveillance to monitor for recurrence and metastasis.